2012
DOI: 10.5755/j01.ct.61.3.2660
|View full text |Cite
|
Sign up to set email alerts
|

Changes of ocular signs in children with thyroid diseases after intake of bee bread

Abstract: The objective of the study was to investigate visual acuity, refractive status and eye proptosis in children with thyroid diseases before and after the intake of bee bread.The investigations of visual acuity refraction and eye proptosis were done in 34 children with thyroid diseases (age range from 6 to 17 years) at the Eye Clinic of the Lithuanian University of Health Sciences Medical Academy. Eighteen patients used bee bread and underwent low-frequency pulsed electromagnetic field therapy. For 16 subjects, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Jarušaitienė et al [ 116 ] studied refractive status, visual acuity, and ocular prophylaxis in 34 children (aged 6 to 17) with thyroid disease before and after taking bee bread. The results of this study showed an increase in visual acuity in the subjects who used bee bread.…”
Section: The Use Of Bee Bread In Clinical Studiesmentioning
confidence: 99%
“…Jarušaitienė et al [ 116 ] studied refractive status, visual acuity, and ocular prophylaxis in 34 children (aged 6 to 17) with thyroid disease before and after taking bee bread. The results of this study showed an increase in visual acuity in the subjects who used bee bread.…”
Section: The Use Of Bee Bread In Clinical Studiesmentioning
confidence: 99%